Adsorption of anionic surfactant on sandstone reservoir containing clay minerals and its effect on wettability alteration - Ira Herawati; Pudji Permadi; Achmad Rochliadi; Taufan Marhaendrajana (Energy Reports, 2022)
Previous researches have shown that different anionic surfactants have different adsorption rates on mineral clays. Furthermore, many literatures have presented that anionic surfactants have little effect in changing the wettability of rocks containing clay minerals compared to cationic and nonionic surfactant. Mainly their experiments used anionic surfactant ethoxylated sulfonate, alkyl benzene sulfonates, sodium dodecyl sulfate, and sodium laureth sulfate. This paper studies the adsorption and its effect of an anionic surfactant alky ethoxy carboxylate (which is almost never discussed) on the wettability of sandstone containing Ca-montmorillonite and kaolinite clays. Some experimental works were conducted to support the analysis that include measurements of contact angle, zeta potential, pH, High-Performance Liquid Chromatography analysis, and SEM-EDX analysis. The results show that sandstones containing kaolinite clay tend to oil-wet and those containing Ca-montmorillonite clay tend to water-wet. The alkyl ethoxy carboxylate (AEC) adsorption that occurs in sandstones containing Ca-montmorillonite and kaolinite clay forms a parabolic curve trend with the minimum at about 15% concentration. The adsorption of AEC was higher by Ca-montmorillonite. Meanwhile, the greater wettability alteration by AEC occurs in sandstone containing kaolinite clay. The relationship between surfactant adsorption and contact angle is inverse, where the higher the surfactant adsorption, the smaller the contact angle value, and vice versa.